Predicting memory scores brain from resting state connectivity - Freitag, Esra (Student Undergraduate Research E-journal!, 2018)
While decades of neuroscientific research has detailed the brain networks underlying memory, to date the neurobiology underlying interindividual memory differences in a healthy population is not known. Here we use the behavioral and resting state fMRI data from the Human Connectome Project (HCP), and predict subjects’ scores on tests of working and episodic memory based on their whole brain functional connectivity significantly above chance. We observed that brain connectivity between regions determining differences between healthy subjects were different from those traditionally associated with memory. Results may ultimately be relevant to determine risk factors for the development of neurodegenerative disorders.